2020
DOI: 10.3390/chemistry2030046
|View full text |Cite
|
Sign up to set email alerts
|

Results in Chemistry of Natural Organic Compounds. Synthesis of New Anticancer Vinca Alkaloids and Flavone Alkaloids

Abstract: The antitumor indole–indoline alkaloids of the evergreen Catharanthus roseus—namely vinblastine and vincristine—are widely used in chemotherapy of cancer. Many efforts were made to synthesize more efficient derivatives with less side-effect. The 14,15-cyclopropane derivative of vinblastine was synthesized successfully by a five-step procedure starting from vindoline. Vincristine, vinorelbine and several derivatives condensed with a cyclopropane ring were synthesized. Various hybrid molecules were prepared by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Hybrid 11 was obtained in this case also via a click reaction. Some of the compounds (11) showed moderate antiproliferative activity on cell line MCF-7 of breast cancer (IC50 = 14.5-19.1 µM), and hybrid 9 (R=CH3, R 1 =H) showed moderate antimycobacterial activity against a bovis strain. The triazole ring is connected to the flavone via an amino group in the following hybrids (Figure 6).…”
Section: Flavone Hybrids With Different Pharmacophoresmentioning
confidence: 99%
See 2 more Smart Citations
“…Hybrid 11 was obtained in this case also via a click reaction. Some of the compounds (11) showed moderate antiproliferative activity on cell line MCF-7 of breast cancer (IC50 = 14.5-19.1 µM), and hybrid 9 (R=CH3, R 1 =H) showed moderate antimycobacterial activity against a bovis strain. The triazole ring is connected to the flavone via an amino group in the following hybrids (Figure 6).…”
Section: Flavone Hybrids With Different Pharmacophoresmentioning
confidence: 99%
“…Important groups of natural compounds are the flavone alkaloids and Vinca alkaloids [11]. Flavone hybrids of vindoline (Figure 14) coupled in position 10 of vindoline (34,35) were synthesized with short or longer linkers.…”
Section: Flavones Coupled With Representative Natural Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors observed the properties of GO and bacterially rGO on cellular survival and in human breast cancer cell. 14,15‐cyclopropanovinorelbine (Scheme 8) has important conclusion in the case of non‐small cell lung cancer, colon cancer, central nervous system cancers, melanoma and human breast cancer [102] . The most effective therapy for breast cancer, cancer in vitro and vivo is volatile organic compounds (VOCs).…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…14,15-cyclopropanovinorelbine (Scheme 8) has important conclusion in the case of non-small cell lung cancer, colon cancer, central nervous system cancers, melanoma and human breast cancer. [102] The most effective therapy for breast cancer, cancer in vitro and vivo is volatile organic compounds (VOCs). Ketones, alcohols, aldehydes, hydrocarbons, isocyanates, terpenes, sulphides, and amines are just a few of the many carbon-based compounds that make up VOCs.…”
Section: Graphene and Go-based Nanocomposite Applications Referencesmentioning
confidence: 99%